2017
DOI: 10.1038/srep43568
|View full text |Cite
|
Sign up to set email alerts
|

A possible role for neutrophils in allergic rhinitis revealed after cellular subclassification

Abstract: A re-examination of former concepts is required to meet today’s medical challenges in allergic rhinitis. Previously, neutrophils have been treated as a relatively homogenous cell population found in the nose both when the patient is suffering at the height of the allergic season as well as when the patient report no symptoms. However, new data indicates that neutrophils can be divided into different subsets with diverse roles in inflammation. We showed increased levels of neutrophils in peripheral blood, nasal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 47 publications
(54 reference statements)
4
47
0
1
Order By: Relevance
“…Notably, similar populations of CD62L low CD16 high neutrophils have been reported in the peripheral blood, nasal biopsies, and nasal lavage fluid of allergic patients [74], as well as in the peripheral blood and bronchoalveolar lavage fluid of infants with different types of viral respiratory infections (e.g., respiratory syncytial virus, bocaviruses, coronavirus, or rhinoviruses) with and without bacterial coinfection (e.g., Haemophilus influenza, Staphylococcus aureus, Streptococcus pneumonia, or Pseudomonas aeruginosa) [75]. However, in the former case (allergy), CD62L low CD16 high neutrophils displayed T cell priming activityrevealed by their ability to increase the expression of CD69 + on naïve CD4 + T cells [74]. In the latter case (viral infections), CD62L low CD16 high neutrophils were defined as immunosuppressive without verifying their ability to inhibit T cell functions in vitro [75].…”
Section: Neutrophils Versus Pmn-mdscs In Cancersupporting
confidence: 75%
See 1 more Smart Citation
“…Notably, similar populations of CD62L low CD16 high neutrophils have been reported in the peripheral blood, nasal biopsies, and nasal lavage fluid of allergic patients [74], as well as in the peripheral blood and bronchoalveolar lavage fluid of infants with different types of viral respiratory infections (e.g., respiratory syncytial virus, bocaviruses, coronavirus, or rhinoviruses) with and without bacterial coinfection (e.g., Haemophilus influenza, Staphylococcus aureus, Streptococcus pneumonia, or Pseudomonas aeruginosa) [75]. However, in the former case (allergy), CD62L low CD16 high neutrophils displayed T cell priming activityrevealed by their ability to increase the expression of CD69 + on naïve CD4 + T cells [74]. In the latter case (viral infections), CD62L low CD16 high neutrophils were defined as immunosuppressive without verifying their ability to inhibit T cell functions in vitro [75].…”
Section: Neutrophils Versus Pmn-mdscs In Cancersupporting
confidence: 75%
“…These cells were found to inhibit proliferation and cytokine [e.g., IFN-γ and interleukin (IL)-13] production by CD4 + and CD8 + T cell in vitro via CD11b-dependent ROS release [8,73]. Notably, similar populations of CD62L low CD16 high neutrophils have been reported in the peripheral blood, nasal biopsies, and nasal lavage fluid of allergic patients [74], as well as in the peripheral blood and bronchoalveolar lavage fluid of infants with different types of viral respiratory infections (e.g., respiratory syncytial virus, bocaviruses, coronavirus, or rhinoviruses) with and without bacterial coinfection (e.g., Haemophilus influenza, Staphylococcus aureus, Streptococcus pneumonia, or Pseudomonas aeruginosa) [75]. However, in the former case (allergy), CD62L low CD16 high neutrophils displayed T cell priming activityrevealed by their ability to increase the expression of CD69 + on naïve CD4 + T cells [74].…”
Section: Neutrophils Versus Pmn-mdscs In Cancermentioning
confidence: 76%
“…IL-17 from Th17 cells was also associated with neutrophil recruitment in AR, probably by inducing IL-8 and CXCL1Groα release by airway fibroblasts. Neutrophils express multiple mediators which mediate airway inflammation such as MMP-9, neutrophil elastase, α-defensin, TGF-ß1 and ROS, supporting eosinophil migration and priming of T cells [ 87 ]. The prolonged release of neutrophil elastase and free radicals damage the epithelium and are most likely responsible for vasomotor symptoms characterizing AR.…”
Section: Blood Cells In Armentioning
confidence: 99%
“…The CD16 high CD62L high ‐expressing neutrophils are mature, but non‐activated, whereas the CD16 high CD62L dim ‐expressing neutrophils are considered to be mature and activated, playing an important role in inflammatory diseases such as systemic inflammation . Subsets of neutrophils with similar antigen presentation characteristics have been produced in vitro using LPS and we have shown that these subsets have specific roles in allergic rhinitis and head and neck squamous cells cancer …”
Section: Introductionmentioning
confidence: 98%